Allanite U–Pb step-leaching ages of metapelites in the Imjingang belt, central Korea - Seunghee Han; Yoonsup Kim; Taehoon Kim; Mi Jung Lee (Journal of Analytical Science and Technology)
Abstract Background Allanite is a LREE-rich epidote-group mineral, and a potential chronometer for the greenschist-facies metamorphism. However, owing to the metamict nature of allanite, it is extremely difficult to secure sufficient amounts of mineral separates from metapelites. Thus, we applied the U–Pb step-leaching (UPbSL) technique to determine the metamorphic age of allanite inclusions in garnet porphyroblasts, 1–2 mm long in diameter, separated from kyanite–staurolite–garnet schists in the Imjingang belt, central Korea. Methods The UPbSL dating on the garnet separates was performed with seven individual steps as a function of variable type and concentration of acid, temperature, and time. In particular, HCl was used to dissolve garnet separates in the steps 1 to 4, whereas HBr in the rest of steps. Leaching by HF was avoided in the experiments to minimize detrital zircon contribution to the U–Pb isotopic systematics. Following the UPbSL, column chromatography was carried out using the AG1X 100–200 mesh ion exchange resin with 6 N HCl for Pb and the AG1X 200–400 one with 8 N HNO3 and distilled water for U, respectively. The U–Pb isotopic compositions of leachates at each step were measured using thermal ionization mass spectrometry in addition to 208Pb–235U and 205Pb–235U mixed spikes. Results The U and Pb concentrations in the UPbSL analyses range from the several tens to hundreds ppb, and isotopic fractionation in this study was minor including 238U/204Pb ratios in the range of ~ 10–100 which resulted in large uncertainties in the errorchron ages. The 208Pb/206Pb and 207Pb/206Pb ratios in the analyses show a linear correlation which suggests a mixing between the single radiogenic Pb and common Pb components. Errorchron ages of 269 ± 140 Ma (2σ) and 290 ± 280 Ma (2σ) were obtained from the 100-mg and 200-mg UPbSL experiments with initial ratios of 17.4 ± 1.4 and 17.3 ± 2.5, respectively. Conclusions The UPbSL data in this study demonstrate that both U and radiogenic Pb originate predominantly from allanite inclusions within garnet and yielded the U–Pb allanite age of ~ 270–290 Ma. The ages are similar to the chemical age of monazite (255 ± 8 Ma) in the same schistose unit and the U–Pb age of zircon (253 ± 2 Ma) from a paragneiss in the Imjingang belt. Therefore, the UPbSL is applicable to measuring metamorphic ages of allanite in metapelites.